PROTOTIPE KNOWLEDGE MANAGEMENT SYSTEM BERBASIS E-BUSINESS: STUDI KASUS MARGATEKNO OFFICIAL CENTER - FIQIH ISMAWAN; PUPUT IRFANSYAH (LPPM, 2015)
Suppression will be increasingly important quality of human resources is one of the responses in addressing the changes of the effects of globalization and the development of information technology which greatly accelerated, of course this requires a special effort to improve and develop human resources. Knowledge has become something which is crucial, therefore, the acquisition and utilization needs to be managed properly in the context of enterprise performance improvement. The move is seen as something that is very strategic in the face of global competition, therefore we need a way to integrate that knowledge in a range of human resource development within the company. Then look at the issue a decision that can be done is to create a method of human resource development using UML as a prototype and model of the design and implementation of knowledge management system that will be the development of human resources and corporate business. The results of this analysis to increase the capacity of human resource knowledge can certainly be used in the company's decision making. Keywords: Prototype, Knowledge, Knowledge Management System, UML